UPAYA PENINGKATAN SOFT SKILL PESERTA DIDIK SESUAI TANTANGAN ABAD XXI DI SMK NEGERI PERTANIAN KOTA SERANG - bohari, bohari; Ikhsanudin, Ikhsanudin; Shodiq, Dzulatif As (Educational Technology Journal, 2024)
Vocational Schools also aim to produce human resources who are intellectual and ready to use in the world of work. Therefore, to prepare students who are able to compete in the 21st century is the responsibility of Indonesian educational institutions by implementing or equipping them with 4C competencies through superior programs. This research method uses a qualitative approach with a narrative study method. The purpose of this research is to find out the efforts made by schools to improve students' soft skills in the challenges of the 21st century. The findings of this research are regarding efforts to improve students' soft skills with several programs created by schools, including the existence of extracurriculars, literacy Fridays, P5 program (project to strengthen the profile of Pancasila students). apart from that, it is also to improve soft skills through entrepreneurship learning which is included in the Creative Products and Entrepreneurship (PKK) subjects.).